PERBEDAAN PERSEPSI KETERTARIKAN INTERPERSONAL SISWA PADA GURU SEKOLAH DASAR BERDASARKAN UKURAN TUBUH - GUMGUM GUMELAR; CINTYA GUSWIANANDA NUGRAHENI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2015)
This study aims to determine whether there is a difference in perceptions of interpersonal attractiveness of students in primary school teachers in Pondok Kelapa East Jakarta based on body size. This research uses quantitative approach with pre-experimental research method and quota sampling technique and questionnaire as data. This experiment was designed with digital manipulation of male and female teacher body size images as a stimulus variation, which then compares between variations and selected using the guttman scale with option 1 or 2. Then in rating with likert scale to know the level of interest. Subject of this study there are 155 people with age 18-12 years. The result of statistical analysis that yield is F = 28,284, p = 0,000 <0,05 (significant). The results showed a significant difference perceptions of interpersonal interest of students in elementary school teachers according to body size.